Innateness as a natural cognitive kind. (2nd April 2016) - Khalidi, Muhammad Ali
Abstract: Innate cognitive capacities are widely posited in cognitive science, yet both philosophers and scientists have criticized the concept of innateness as being hopelessly confused. Despite a number of recent attempts to define or characterize innateness, critics have charged that it is associated with a diverse set of properties and encourages unwarranted inferences among properties that are frequently unrelated. This criticism can be countered by showing that the properties associated with innateness cluster together in reliable ways, at least in the context of the study of cognition (though perhaps not in other scientific domains). Even though the causal connections between these cognitive properties are not always strict, they are robust enough to warrant considering innateness to be a natural kind as used in contemporary cognitive science.